Evaluation of phosphate depressants in the phosphate - Zhang, P. (Minerals & Metallurgical Processing : An International Peer-Reviewed Journal)
The use pf phosphate depressant in the cationic flotation of silica from francolite in the Florida phosphate industry is rarely practiced. The occasional use of gelatinized starch derivatives and pH adjustments to assure a slightly alkaline flotation feed slurry pH have been used in some processing plants to improve selectivity. This paper presents a preliminary laboratory comparison of several potential phosphate depressants for use with the flotation of siliceous phosphates. It was found that starch is ideal for floating fine (-35 mesh) silica from phosphate, while sodium tripolyphosphate may be the best for coarser (+35 mesh) feeds.